2021
DOI: 10.48550/arxiv.2103.02123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high occurrence of nuclear star clusters in faint Coma galaxies, and the roles of mass and environment

Emilio J. B. Zanatta,
Rubén Sánchez-Janssen,
Ana L. Chies-Santos
et al.

Abstract: We use deep high resolution HST/ACS imaging of two fields in the core of the Coma cluster to investigate the occurrence of nuclear star clusters (NSCs) in quiescent dwarf galaxies as faint as M I = −10 mag. We employ a hierarchical Bayesian logistic regression framework to model the faint end of the nucleation fraction ( f n ) as a function of both galaxy luminosity and environment. We find that f n is remarkably high in Coma: at M I ≈ −13 mag half of the cluster dwarfs still host prominent NSCs. Comparison wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 62 publications
3
9
0
Order By: Relevance
“…Very recently, Zanatta et al (2021) also confirmed this environmental trend comparing satellites in different mass clusters and lower mass, LV hosts. For the latter, they used satellites partly from the surveys of Carlsten et al (2020a,b).…”
Section: Nsc Abundancesupporting
confidence: 55%
See 3 more Smart Citations
“…Very recently, Zanatta et al (2021) also confirmed this environmental trend comparing satellites in different mass clusters and lower mass, LV hosts. For the latter, they used satellites partly from the surveys of Carlsten et al (2020a,b).…”
Section: Nsc Abundancesupporting
confidence: 55%
“…While the inner LV nucleation fractions are still slightly below that of the Virgo sample, the difference is much less. This brings up the intriguing possibility that the difference seen in the left panel and reported by Sánchez-Janssen et al (2019) and Zanatta et al (2021) is actually more of an effect of the cluster samples being very centralized and less due to the parent halo mass in which the dwarfs reside. Unfortunately we do not have the dwarf samples to conclusively show which affect (parent halo mass or location of dwarf within parent halo) is dominant.…”
Section: Nsc Abundancementioning
confidence: 85%
See 2 more Smart Citations
“…This migration can then be followed by a merger with another cluster. Dwarf galaxies are also known to host active galactic nuclei (AGN; e.g, Marleau et al 2013Marleau et al , 2017Kaviraj et al 2019;Mezcua & Domínguez Sánchez 2020;Molina et al 2021) or both NSC and AGN (Côté et al 2006;den Brok et al 2015).…”
mentioning
confidence: 99%